Поліпшення вихідних характеристик планетарних гідромашин - Панченко, Анатолій Іванович; Панченко, Анатолий Иванович; Panchenko, Anatolii; Волошина, Анжела Анатоліївна; Волошина, Анжела Анатольевна; Voloshyna, Anzhela; Панченко, Ігор Анатолійович; Панченко, Игорь Анатольевич; Panchenko, Ihor; Засядько, Андрій Іванович (My University, 2019)
UK: Для вирішення проблеми підвищення технологічності виготовлення елементів розподільної системи планетарного гідромотора обґрунтована форма вікон рухомого та нерухомого розподільників. Розроблено розрахункову схему, математичну модель та алгоритм розрахунку, що дозволяють досліджувати вплив зміни геометричних параметрів розподільної системи з вікнами, виконаними у вигляді кола, на пропускну здатність планетарного гідромотора. Встановлено, що в залежності від кінематичної схеми розподільної системи площа прохідного перетину розподільної системи змінюється. При цьому змінюється і амплітуда коливань площі прохідного перетину. При використанні розвантажувальних вікон розподільника в якості додаткових робочих вікон, пропускна здатність збільшується, а амплітуда коливань – зменшується. Критичним параметром, що визначає працездатність розподільної системи, є коливання площі прохідного перетину. Тому, при проектуванні розподільних систем рекомендується використання додаткових розвантажувальних вікон в якості робочих. RU: для решения проблемы повышения технологичности изготовления элементов распределительной системы планетарного гидромотора обоснована форма окон подвижного и неподвижного распределителей. Разработаны расчетная схема, математическая модель и алгоритм расчета, позволяющие исследовать влияние изменения геометрических параметров распределительной системы с окнами, выполненными в виде окружности, на пропускную способность планетарного гидромотора. Установлено, что в зависимости от кинематической схемы распределительной системы площадь проходного сечения распределительной системы изменяется. При этом изменяется и амплитуда колебаний площади проходного сечения. При использовании разгрузочных окон распределителя в качестве дополнительных рабочих окон, пропускная способность увеличивается, а амплитуда колебаний – уменьшается. Критическим параметром определяющим работоспособность распределительной системы являются колебания площади проходного сечения. Поэтому, при проектировании распределительных систем рекомендуется использование дополнительных разгрузочных окон в качестве рабочих. EN: One of the main systems limiting the work of a planetary hydraulic motor is its distribution system. The distribution system of such a hydraulic motor consists of fixed and movable distributor. The fixed distributor serves to supply (drain) the working fluid in the planetary hydraulic motor. It is mounted fixed relative to the motor case. The movable distributor serves to supply (drain) the working fluid to the working chambers of the hydraulic motor. It is mounted on the hydraulic motor shaft and rotates relative to the fixed distributor. The efficiency of the distribution system depends on the manufacturability of its elements. To solve the problem of improving the manufacturability of the elements for the distribution system of a planetary hydraulic motor, the shape of the windows of the movable and fixed distributors is justified. A design diagram, a mathematical model and a calculation algorithm have been developed as well. That allowed to investigate the effect of changes in the geometric parameters of the distribution system on a planetary hydraulic motor throughput when the windows are made in the form of a circle. It has been established that the flow area of the distribution system varies according to the kinematic diagram of the distribution system. At the same time, the amplitude of the flow area oscillations changes as well. When using the discharging windows of the distributor as additional working windows, the throughput increases, and the amplitude of oscillations decreases. The critical parameter which determines the operability of the distribution system is the oscillations of the flow area. Therefore, when designing distribution systems, it is recommended to use additional discharging windows as working ones.
Улучшение выходных характеристик планетарных гидромашин
Improving the output characteristics of planetary hydraulic machines
Keywords: планетарний гідромотор; пропускна здатність; розподільна система; розподільні вікна; пропускна здатність; кінематична схема